miR-4698-Trim59 axis plays a suppressive role in hepatocellular carcinoma - Dandan Yu (Frontiers in Bioscience-Landmark, 2020)
microRNAs (miRNAs) are important in tumor suppression and oncogenesis. In this study, we aimed to explore the role of miR-4698 with its potential target, Tripartite motif-containing 59 (Trim59), a protein with oncogenic function, in hepatocellular carcinoma (HCC). The expression of miR-4698 was significantly lower in HCC tissues and HCC cell lines as compared to the levels expressed in normal tissues adjacent to tumors and in normal hepatic cell line. Overexpression of miR-4698 in HCC cells by transfection of its mimic significantly inhibited cell growth, migration, invasion and epithelial-mesenchymal transition (EMT), whereas, its antisense oligonucleotides (ASOs) exerted an opposite effect. Trim59 was identified as a target of miR-4698 in miRDB and consistent with this, the expression of Trim59 was inversely correlated with miR-4698 in HCC, and miR-4698 overexpression led to a significant decrease in luciferase activity of pRL-Trim59-3’-UTR, but not mutant pRL-Trim59-3’-UTR. Moreover, miR-4698 mimic inhibited the expression of Trim59. Overexpression of Trim59 abrogated the inhibitory effects of miR-4698. In conclusion, these data show that miR-4698-Trim59 axis plays a tumor suppressive role in HCC.